PENGUJIAN KADAR AIR DAN KUAT TARIK BAMBU GORONTALO - Sartika Dewi Usman (CV. Denasya Smart Publisher, 2025)
This study aims to examine the moisture content and tensile strength of Gorontalo bamboo as an alternative construction material that is environmentally friendly and economical. Bamboo samples were taken from the end part with moisture content testing using an oven and tensile strength testing using a tensile strength machine. The results showed the moisture content of Gorontalo bamboo and the tensile strength value that can be a reference in the utilization of bamboo as a building structure material. This research is expected to provide scientific information that is beneficial for the development of bamboo as a sustainable construction material.